COMPARISON OF DIFFERENT APPROACHES TO POPULATION EXPOSURE LIMITATION AT RADIOACTIVE CONTAMINATION OF THE ENVIRONMENT (AT THE EXAMPLE OF EXTERNAL EXPOSURE ON TERRITORIES CONTAMINATED AFTER THE CHERNOBYL ACCIDENT) - V. Yu. Golikov (Радиационная гигиена)
The article is dedicated to comparison of different approaches to population exposure limitation at the example of external exposure of population living on territories contaminated after the accident at Chernobyl NPP. On the basis of the earlier developed model of population external exposure from Chernobyl fallout, the following criteria already being used in Russia or recommended by International Commission on Radiological Protection were compared:• Average dose in critical group of population;• Average dose of 10% of the settlement population having highest individual doses compared to others;• The Representative Person concept The value of the relation of annual effective dose calculated according to these approaches to the average dose for all the population of the settlement is between 1.7 and 1.85.